The Effectiveness of Using Instagram as Teaching Tools in Learning Process of 3rd Semester of English Department Students - Siti Isma Sari Lubis; Fitri Rayani Siregar; Maryati Salmiah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2020)
Online learning is one of the big challenges that must be done in this Era. However many people less access and do not use the appropriate media to do it. Besides, they also lack of the application usage. However, Social Media is more popular today. Many people spend their time on social media for communicating, entertaining, selling, and etc. Therefore, using social media as the tool to do the communication in learning is possible to do. One of the popular social media that is used by the students today is Instagram, which has 70 million users in Indonesia. Thus, this research is aimed to find out the effectiveness of using Instagram in online learning. It is specified to the 3rd Semester students of English Department of IAIN Padangsidimpuan. It investigated the participation and feedback of students in learning process while using Instagram as the platform in learning activity. This research used descriptive qualitative research to analyse the students’ perception in implementing Instagram in learning process. The results show that Instagram is effective to be used as the tool for the students’ interaction especially in discussion which is related to the task activity and explanation. Besides, the students felt easier to use this application because it has been used by almost students of the 3rd semester of English Department of IAIN Padangsidimpuan.